Eksistensi Filsafat dan Mantiq (Logika) dalam Pengembangan Ilmu Keislaman Era 5.0 - Sarah Dina; Firdaus, Muhammad (Jurnal Filsafat Indonesia, 2023)
Evaluation of Islamic science in its future development is carried out by studying the influence of mantiq science in the formation of Islamic sciences. Modern thinking in the 5.0 era is synonymous with the existence of Mantiq (logic) and the structure and rules of rational thinking. This research focuses on examining how the impact of mantiq on Islamic sciences in the past can be used as an indicator in determining whether mantiq knowledge (logic) is still valid or not for the development of modern science and Islamic studies in the current 5.0 era. This study uses a qualitative method with library research or literature review. Sources of data in this study into two parts, namely primary data and secondary data. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this study indicate that mantiq or logic has a great influence on the development of Islamic studies in this era, especially in the study of aqidah, fiqh, and kalam. Many scientific works resulted from the implementation of mantiq, the development of mantiq science is inseparable from Islamic philosophy, the existence of mantiq or logic has developed very rapidly in the Islamic scientific world and has had an impact on human life since its emergence in the ancient Greek era.